Evaluating bioenergetic pathway contributions from single to multiple sprints - Süleyman Ulupınar; Serhat Özbay; Cebrail Gençoğlu; Ibrahim Ouergui; Furkan Öget; Necip Fazıl Kishalı; Fatih Kıyıcı; Hasan Hüseyin Yılmaz; Luca Paolo Ardigò (Scientific Reports)
Abstract This study aims to investigate the changes in bioenergetic pathway contributions during repeated sprint exercises with an increasing number of repetitions. Twelve male amateur soccer players executed a single 20 m sprint and three repeated-sprint protocols (5 × 20 m, 10 × 20 m, 15 × 20 m with 15-second rest intervals), analyzing oxidative, glycolytic, and ATP-PCr energy pathways using the PCr-LA-O2 method. Findings revealed a significant decline in energy expenditure and performance outputs as the number of sprint repetitions increased. While the oxidative and ATP-PCr pathways’ energy contributions significantly rose with more sprints, the glycolytic pathway’s contribution notably increased only up to the 10 × 20 m protocol, then stabilized. Although the ATP-PCr pathway’s energy contribution decreased slightly from sprints 1–5 to 11–15, it remained significantly higher than the oxidative and glycolytic pathways throughout. Initially, glycolytic contribution surpassed oxidative in sprints 1–5, equaled it in sprints 6–10, and fell below in sprints 11–15. Glycolytic activity, a major energy source initially (about 36%), diminished substantially with more sprints (below 7% in the 15th sprint). This indicates that the decrease in non-mitochondrial pathway energy, particularly glycolytic, outstrips the aerobic system’s increased tolerance. These findings offer physiological insights into the relationship between performance decrement and bioenergetic metabolism in repeated sprints.